2015
DOI: 10.5603/fm.a2018.0057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitro-oleic versus losartan in diabetic nephropathy: modulation of parathyroid hormone related protein

Abstract: Both pre and post-DN losartan, NO2-OA may have a potential role in protection and regression of DN through reduction of PTHrP overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…11 studies [ 6 , 7 , 10 , 12 , 16 , 20 – 22 , 24 , 26 , 31 ] analyzed urinary albumin. Meta-analysis results showed that MD = −52.68, 95% CI (-77.78, -27.59), P < 0.0001, and I 2 = 97%.…”
Section: Resultsmentioning
confidence: 99%
“…11 studies [ 6 , 7 , 10 , 12 , 16 , 20 – 22 , 24 , 26 , 31 ] analyzed urinary albumin. Meta-analysis results showed that MD = −52.68, 95% CI (-77.78, -27.59), P < 0.0001, and I 2 = 97%.…”
Section: Resultsmentioning
confidence: 99%
“…Another study has shown that administration of losartan to DN model rat resulted in improvements in systolic blood pressure, serum glucose, urea, GFR, and a decrease in serum Ang-II levels. Histopathological results showed clear improvement in glomerulosclerosis, vascular and tubular injury parameters in the losartan group (28).…”
Section: Discussionmentioning
confidence: 86%